Transcriptome analysis of antigenic variation in Plasmodium falciparum - var silencing is not dependent on antisense RNA - Ralph, Stuart A; Bischoff, Emmanuel; Mattei, Denise; Sismeiro, Odile; Dillies, Marie-Agnès; Guigon, Ghislaine; Coppee, Jean-Yves; David, Peter H; Scherf, Artur (Genome biology, 2005)
Plasmodium falciparum, the causative agent of the most severe form of malaria, undergoes antigenic variation through successive presentation of a family of antigens on the surface of parasitized erythrocytes. These antigens, known as Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) proteins, are subject to a mutually exclusive expression system, and are encoded by the multigene var family. The mechanism whereby inactive var genes are silenced is poorly understood. To investigate transcriptional features of this mechanism, we conducted a microarray analysis of parasites that were selected to express different var genes by adhesion to chondroitin sulfate A (CSA) or CD36. In addition to oligonucleotides for all predicted protein-coding genes, oligonucleotide probes specific to each known var gene of the FCR3 background were designed and added to the microarray, as well as tiled sense and antisense probes for a subset of var genes. In parasites selected for adhesion to CSA, one full-length var gene (var2csa) was strongly upregulated, as were sense RNA molecules emanating from the 3' end of a limited subset of other var genes. No global relationship between sense and antisense production of var genes was observed, but notably, some var genes had coincident high levels of both antisense and sense transcript. Mutually exclusive expression of PfEMP1 proteins results from transcriptional silencing of non-expressed var genes. The distribution of steady-state sense and antisense RNA at var loci are not consistent with a silencing mechanism based on antisense silencing of inactive var genes. Silencing of var loci is also associated with altered regulation of genes distal to var loci.